Amelioration of experimental autoimmune encephalomyelitis by anatabine. - Daniel Paris; David Beaulieu-Abdelahad; Myles Mullan; Ghania Ait-Ghezala; Venkat Mathura; Corbin Bachmeier; Fiona Crawford; Michael J Mullan (PLoS ONE, 2013)
Anatabine, a naturally occurring alkaloid, is becoming a commonly used human food supplement, taken for its claimed anti-inflammatory properties although this has not yet been reported in human clinical trials. We have previously shown that anatabine does display certain anti-inflammatory properties and readily crosses the blood-brain barrier suggesting it could represent an important compound for mitigating neuro-inflammatory conditions. The present study was designed to determine whether anatabine had beneficial effects on the development of experimental autoimmune encephalomyelitis (EAE) in mice and to precisely determine its underlying mechanism of action in this mouse model of multiple sclerosis (MS). We found that orally administered anatabine markedly suppressed neurological deficits associated with EAE. Analyses of cytokine production in the periphery of the animals revealed that anatabine significantly reduced Th1 and Th17 cytokines known to contribute to the development of EAE. Anatabine appears to significantly suppress STAT3 and p65 NFκB phosphorylation in the spleen and the brain of EAE mice. These two transcription factors regulate a large array of inflammatory genes including cytokines suggesting a mechanism by which anatabine antagonizes pro-inflammatory cytokine production. Additionally, we found that anatabine alleviated the infiltration of macrophages/microglia and astrogliosis and significantly prevented demyelination in the spinal cord of EAE mice. Altogether our data suggest that anatabine may be effective in the treatment of MS and should be piloted in clinical trials.